Die toratreue Susanna schämt sich ihrer Nacktheit nicht: „Susanna ohne Scham“ im Kontext der abendländischen Malerei - Fischer, Irmtraud (Die Bibel in der Kunst, 2021)
This article traces representations of the deuterocanonical narrative of Susanna in European painting. In present-day Catholic Bible translations, the text of Dan 13 is not to be found in the Septuagint version but in that of Theodotion, as it was translated from the Vulgate. The Septuagint narrates the story far more matter-of-factly, its theological focus is on Susanna as law-abiding Jewish woman. Theodotion, however, embellishes the storyline sensually, here, Susanna’s faithfulness primarily applies to her husband. Representations of Susanna in Western art are multifarious as can be seen as early as in the paintings of the Roman catacombs. In baroque art, the then very popular motif of „Susanna and the Elders“ is depicted as a female nude which places the viewer in the position of a voyeur. But also in that epoch, variations do exist: The author of this article is looking into a type of paintings created by Antoine Coypel that is documented several times and which she calls „Susanna without pudency“. This type of paintings is closer to the tenor of the Septuagint version than to Theodotion’s. However, direct dependency is unlikely, for the Greek version was hardly known even in scholarly circles at the time.